The estimation of GHG emission costs in road and air transport sector: case study of Serbia - Ivković, Ivan; Čokorilo, Olja; Kaplanović, Snežana (Transport, 2018)
The paper gives special attention on long distance passenger transport and specific emissions related to different transport modes, particularly road and air transport sector. The goal of this research is creation and selection of appropriate methodology for modelling the cost estimation of GHG emissions in road and air transport sector for Republic of Serbia as well as the application of the methodology regarding to detailed calculation by transport mode and sub modes. Input data for road transport sector refer to the 2013 and include road and traffic conditions on the road network. Input data for air transport sector are related to the 2014 and international airport ‘Nikola Tesla’ Belgrade as the main hub point with the highest recorded number of aircraft operations in the Western Balkan countries. The obtained results reveal that, due to realized transport volume, diesel cars have the largest share of the costs of GreenHouse Gas (GHG) emissions within the passenger long distance road transport. Cost estimates of CO2 emissions in the air transport sector shows that A319 aircraft type have the major share in total costs. The reasons are twofold: first, a high level of Landing and Take-Off (LTO) emission factor for CO2 and second, largest number of LTO cycles.First published online 11 April 2016